How Philanthropy Is Changing in Europe - Carnie, Christopher (Book collections on Project MUSE., 2017)
Complete with a substantial appendix of sources, this book helps readers understand the revolution in philanthropy in Europe and provides market information for anyone building strategies for fundraising or philanthropy.